ANALISIS KEUNTUNGAN PRODUSEN BABI PUTAR DI KECAMATAN TUMINTING KOTA MANADO (Studi Kasus Usaha Babi Putar Simponi) - Gura, Febrion; Pangemanan, S P; Kalangi, J K.J; Lumenta, I D.R (Universitas Sam Ratulangi, 2020)
ABSTRACTPROFIT ANALYSIS OF PRODUCER FOR ROASTED PORK AT TUMINTING DISTRICT OF MANADO(Case Study at Simponi Roasted Roll Pork Business). Study was done to evaluate profit of roasted Roll Pork business in Tuminting district of Manado. Study was conducted on February 1 to 28, 2019. Data were collected based on case study with survey method. Data were analyzed by descriptive method to describe the profit of Simponi roasted roll pork trade. Results showed that owner characteristic of Simponi roasted roll pork trade was categorized into productive age with education level of high school and the experience of 12 years on roasted roll pork trade. Processing of roasted roll pork was initiated of slaughtering and dressing carcass of entrails with the whole intact body condition. The whole carcass body condition was sticked using roll sticker from mouth to the anus part of animal. Parts of mouth and four legs were tied into sticker. The whole animal body and stomach area were lubricated with cooking spices. These entire spicy lubricated carcasses under sticker were roasted above warmer fire done under rolling sticker. The white skin color was gradually changing into red-brownish color and soft tender skin indicating well done roasted roll pork. The well done roasted roll pork was wraped and ready to be served on dish of food offered to the consumers. The total cost spent providing roasted roll pork at Simponi were IDR 353.843.447 per year.-. The total revenue were IDR 508.200.000 per year.-. Therefore, the profits were IDR 154.356.553 per year.